2018
DOI: 10.1002/ajh.25025
|View full text |Cite
|
Sign up to set email alerts
|

Ataluren‐driven restoration of Shwachman‐Bodian‐Diamond syndrome protein function in Shwachman‐Diamond syndrome bone marrow cells

Abstract: Shwachman-Diamond syndrome (SDS) is a rare inherited recessive disease mainly caused by mutations in the Shwachman-Bodian-Diamond syndrome (SBDS) gene, which encodes for the homonymous protein SBDS, whose function still remains to be fully established. SDS affects several organs causing bone marrow failure, exocrine pancreatic insufficiency, skeletal malformations, and cognitive disorders. About 15% of SDS patients develop myelodysplastic syndrome (MDS) and are at higher risk of developing acute myeloid leukem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…Ataluren has shown to produce full length, functional dystrophin ( 2 , 4 , 13 ) in the nonsense mutation mdx mouse and sapje zebrafish models of DMD. Ataluren activity has also been demonstrated in multiple cell‐based and animal disease models of other nonsense mutation genetic disorders, corroborating its ability to promote readthrough of premature stop codons and its potential for treating genetic disease caused by nonsense mutations 14–19 . Comprehensive nonclinical studies have been conducted in safety pharmacology and secondary pharmacodynamics, pharmacokinetics and metabolism, and toxicology programs.…”
Section: Introductionmentioning
confidence: 83%
“…Ataluren has shown to produce full length, functional dystrophin ( 2 , 4 , 13 ) in the nonsense mutation mdx mouse and sapje zebrafish models of DMD. Ataluren activity has also been demonstrated in multiple cell‐based and animal disease models of other nonsense mutation genetic disorders, corroborating its ability to promote readthrough of premature stop codons and its potential for treating genetic disease caused by nonsense mutations 14–19 . Comprehensive nonclinical studies have been conducted in safety pharmacology and secondary pharmacodynamics, pharmacokinetics and metabolism, and toxicology programs.…”
Section: Introductionmentioning
confidence: 83%
“…Furthermore, ataluren has shown less toxicity and better safety tolerability than aminoglycosides [212,214]. This last feature arises from the fact that ataluren displays its therapeutic activity at concentration much lower (i.e., 3 µM) than gentamicin (i.e., 1 mM) and other aminoglycosides [5,178,197]. It has been demonstrated that the readthrough efficacy of ataluren depends on the sequence of the premature termination codon (PTC) (UAA<UAG<UGA) as well as the sequences of the flanking regions of PTC [195,196,215].…”
Section: Ataluren and Analoguesmentioning
confidence: 99%
“…Finally, nonsense suppression efficiency may depend on the NMD. The readthrough activity sustained by ataluren was reported in several studies both in vivo and in vitro [189,192,196,197,200,214], but the mechanism of action of ataluren in cells harboring nonsense mutation remains poorly understood [195,216,217], beyond its proposed interaction with mRNA [218]. The use of ataluren as a potential therapeutic agent for genetic disorders has been early proposed for the treatment of DMD and CF [192,193,214].…”
Section: Ataluren and Analoguesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonsense mutations are found in about 11% of genetic disorders such as cystic fibrosis (CF) [ 17 ], Duchenne muscular dystrophy (DMD) [ 18 ], spinal muscular atrophy [ 19 , 20 ], neurofibromatosis [ 21 ], retinitis pigmentosa [ 22 , 23 , 24 ], lysosomal storage disease [ 13 , 25 , 26 ], Rett syndrome [ 27 ], Shwachman–Diamond syndrome [ 28 , 29 ], and Usher’s syndrome (USH) [ 30 ]. In this context and despite its limits, the translational readthrough of PTCs can represent a valuable pharmaceutical approach to target the specific genetic defect caused by nonsense mutations.…”
Section: Introductionmentioning
confidence: 99%